Dentro de la línea (2018)
The city is the portion of the land which a vast number of people inhabit in order to create benefits for one another and generally upgrade their living conditions. However, it seems as if the city is actually filled with a series of systems responsible for creating bad experiences and troublesome spaces. Due to the extensive amount of space and sub-structures that it requires, the city's transportation infrastructure is commonly blamed for this condition. Another factor for this problem is the way human beings have chosen to travel across the city, prioritizing long distances and high speeds, but dismissing the human scale and what it requires. Nonetheless, it is impossible to discard these massive bodies of infrastructure, as they are crucial for the city's performance. As a result, a considerable dilemma arises between two equally important components of the city. "Dentro de la Línea" is a project that deals with...